2016
DOI: 10.1002/hyp.10916
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying aggregation and change in runoff source in accordance with catchment area increase in a forested headwater catchment

Abstract: There has been a great deal of research interest regarding changes in flow path/runoff source with increases in catchment area. However, there have been very few quantitative studies taking subscale variability and convergence of flow path/runoff source into account, especially in relation to headwater catchments. This study was performed to elucidate how the contributions and discharge rates of subsurface water (water in the soil layer) and groundwater (water in fractured bedrock) aggregate and change with ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(50 citation statements)
references
References 35 publications
8
42
0
Order By: Relevance
“…Also, at Krycklan, Peralta‐Tapia et al () reported increasing contributions from deeper groundwater sources with increasing catchment area during winter baseflow. Similar increases in groundwater contributions with increasing catchment area during baseflow were observed in a forested catchment in Japan by Egusa, Ohte, Oda, and Suzuki () and in the southern Rocky Mountains by Frisbee, Phillips, Campbell, Liu, and Sanchez (). Nevertheless, the spatial variation in groundwater contributions and the specific physical properties that control the variability in water storage and drainage in headwater catchments during dry periods are still not well understood (e.g., Bishop et al, ; McClymont, Hayashi, Bentley, & Liard, ; Pfister et al, ; Smakhtin, ; Tague & Grant, ).…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…Also, at Krycklan, Peralta‐Tapia et al () reported increasing contributions from deeper groundwater sources with increasing catchment area during winter baseflow. Similar increases in groundwater contributions with increasing catchment area during baseflow were observed in a forested catchment in Japan by Egusa, Ohte, Oda, and Suzuki () and in the southern Rocky Mountains by Frisbee, Phillips, Campbell, Liu, and Sanchez (). Nevertheless, the spatial variation in groundwater contributions and the specific physical properties that control the variability in water storage and drainage in headwater catchments during dry periods are still not well understood (e.g., Bishop et al, ; McClymont, Hayashi, Bentley, & Liard, ; Pfister et al, ; Smakhtin, ; Tague & Grant, ).…”
Section: Introductionsupporting
confidence: 75%
“…They observed high variability in streamwater chemistry that was driven by geology, soils and vegetation at small scales (<2-km distance from the measurements), and less variable streamwater chemistry on larger scales. Exfiltration of deeper groundwater can also affect streamwater chemistry, even at larger scales (e.g., Egusa et al, 2016;Frisbee et al, 2011;Katsuyama, Tani, & Nishimoto, 2010;Peralta-Tapia et al, 2015). Thus, it is important to study the spatial variability in streamflow and stream chemistry across a range of scales to gain insight into the landscape characteristics of the dominant streamflow-generating areas (Blöschl, 2001;McDonnell et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Water Resources Research specific discharge with area. Furthermore, the increase in specific discharge with increasing catchment size in a steep catchment is likely caused by a commensurate increase in the contribution of deep groundwater (e.g., Egusa et al, 2016;Shaman et al, 2004), but other causes are possible. Spatial variation in precipitation affects stream flow (e.g., Singh, 1997), although these effects have not been tested for the relationship between area and specific discharge in mesoscale catchments.…”
Section: 1029/2019wr025658mentioning
confidence: 99%
“…In this study, we focused on the pattern of increasing specific discharge with catchment area (Figure 1b). Previous studies using geochemical tracers have shown that an increase in specific discharge is associated with increased deep groundwater/bedrock groundwater exfiltration (Egusa et al, 2016; Fujimoto et al, 2016; Shaman et al, 2004), which is less significant or absent in smaller catchments. Groundwater in weathered or fractured bedrock can contribute substantially to the response of runoff to rainfall in small catchments in steep headwaters (e.g., Anderson et al, 1997; Komatsu & Onda, 1996; Onda et al, 2001, 2006; Uchida et al, 2003).…”
Section: Introductionmentioning
confidence: 97%
“…Later, Uchida, Asano, Onda, and Miyata () argued that spatial variability of hydrologic response was largely due to flow paths and contributions of bedrock flow in hillslopes and zero‐order basins; variability was dampened in larger catchments, while the bedrock contributions and preferential flow paths occurred at discreet locations along channels. Based on distributed investigations in channel networks (including zero‐order basins and headwater channels), patterns of spatial variability were also assessed by combinations of flow volume and geochemical signatures (Asano, Uchida, Mimasu, & Ohte, ; Egusa, Ohte, Oda, & Suzuki, ). As such, examining the extension from zero‐order basins to larger catchments highlights the unique response and importance of zero‐order basins in the larger catchment context.…”
Section: Linking Zero‐order Basins To Larger Catchmentsmentioning
confidence: 99%